2022
DOI: 10.1021/acs.inorgchem.2c03916
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Carbon Sphere Chain–MnO2 Nanorods as Bifunctional Oxygen Electrocatalysts for Rechargeable Zinc–Air Batteries

Abstract: It is now recognized that the development of selfsupported and efficient bifunctional air cathodes via the direct growth of earth-abundant catalysts onto the surface of the conductive collector would be a cutting-edge strategy to reduce interfacial resistance, enhance the mechanical tenure, and reduce the final weight and cost of manufacturing of rechargeable Zn−air batteries (ZABs). This work reports an innovative self-supported precious metal-free electrode, comprising carbon sphere chains (CSCs) directly gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…As the consumption of conventional fossil fuels increases dramatically, the search for green, efficient, and renewable energies has become a vital issue for the sustainable development of human society. Meanwhile, with the growing demand for wearable electronics, it is also increasingly essential to explore flexible energy storage devices that are flexible, lightweight, safe, high energy storage, long-life, and mechanically stable. , Metal-air batteries, especially zinc-air batteries (ZABs), are considered ideal energy storage systems for electric vehicles, grid energy storage, wearable portable devices, and other areas by virtue of their high theoretical energy density, reliable safety, low cost, and environmental friendliness. Previous studies have demonstrated that electrochemical oxygen evolution reaction (OER) plays a crucial role in metal-air batteries and other sustainable energy conversion and storage devices. , Because of the multi-step proton-coupled electron transfer involved, however, the inherently slow kinetics of OER has gravely hindered the development of related technologies. , At present, noble metal-based catalysts, for instance, IrO 2 and RuO 2 , have been demonstrated to effectively promote OER but are still severely plagued by element scarcity, expensive cost, and unsatisfactory stability. , In addition, the polymer binder (Nafion) used for the powder catalysts in ZAB assembly often blocks the active site of nanostructured electrocatalysts and raises interface resistance, which also sets obstacles for high OER catalytic performance. , The preparation of self-supporting catalysts not only facilitates the exposure of active sites and reduces resistance but also enhances the binding force with the substrate to resist severe bubble impact that can occur during the OER process. Consequently, it is of great value to develop cost-effective and additive-free OER catalysts with high efficiency and superior durability for the practical application and popularization of ZABs.…”
Section: Introductionmentioning
confidence: 99%
“…As the consumption of conventional fossil fuels increases dramatically, the search for green, efficient, and renewable energies has become a vital issue for the sustainable development of human society. Meanwhile, with the growing demand for wearable electronics, it is also increasingly essential to explore flexible energy storage devices that are flexible, lightweight, safe, high energy storage, long-life, and mechanically stable. , Metal-air batteries, especially zinc-air batteries (ZABs), are considered ideal energy storage systems for electric vehicles, grid energy storage, wearable portable devices, and other areas by virtue of their high theoretical energy density, reliable safety, low cost, and environmental friendliness. Previous studies have demonstrated that electrochemical oxygen evolution reaction (OER) plays a crucial role in metal-air batteries and other sustainable energy conversion and storage devices. , Because of the multi-step proton-coupled electron transfer involved, however, the inherently slow kinetics of OER has gravely hindered the development of related technologies. , At present, noble metal-based catalysts, for instance, IrO 2 and RuO 2 , have been demonstrated to effectively promote OER but are still severely plagued by element scarcity, expensive cost, and unsatisfactory stability. , In addition, the polymer binder (Nafion) used for the powder catalysts in ZAB assembly often blocks the active site of nanostructured electrocatalysts and raises interface resistance, which also sets obstacles for high OER catalytic performance. , The preparation of self-supporting catalysts not only facilitates the exposure of active sites and reduces resistance but also enhances the binding force with the substrate to resist severe bubble impact that can occur during the OER process. Consequently, it is of great value to develop cost-effective and additive-free OER catalysts with high efficiency and superior durability for the practical application and popularization of ZABs.…”
Section: Introductionmentioning
confidence: 99%
“…7−9 In spite of the good OER catalytic activity achieved by noblemetal-based oxides such as RuO 2 and IrO 2 , their expensive cost and lack of durability continue to hinder the promotion of related energy technologies. 10,11 In addition, the electrode materials for current rechargeable ZABs are mostly prepared by the traditional pressing process and the addition of binders, which lead to problems like non-bendability, low energy density, poor cycling stability, etc., limiting their practical application in flexible ZABs. 12 Therefore, it becomes imperative to explore non-precious metal self-supporting catalysts with high activity, strong stability, and superior flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The imminent energy crisis and environmental issues are driving the development of highly efficient and environment-friendly clean energy conversion and storage technologies. , Rechargeable Zn–air batteries (ZABs) are attracting widespread interest in grid energy storage, future new energy vehicles, and medical applications due to their cost-effectiveness, a high theoretical energy density of up to 1086 W h kg –1 , excellent security, and eco-friendliness. , In particular, flexible ZABs are expected to serve as a new generation of portable power sources for wearable devices. , Research suggests that the oxygen evolution reaction (OER) is a critical process in ZABs and other new energy technologies but is restricted by sluggish kinetics and high overpotentials. In spite of the good OER catalytic activity achieved by noble-metal-based oxides such as RuO 2 and IrO 2 , their expensive cost and lack of durability continue to hinder the promotion of related energy technologies. , In addition, the electrode materials for current rechargeable ZABs are mostly prepared by the traditional pressing process and the addition of binders, which lead to problems like non-bendability, low energy density, poor cycling stability, etc., limiting their practical application in flexible ZABs . Therefore, it becomes imperative to explore non-precious metal self-supporting catalysts with high activity, strong stability, and superior flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Furthermore, its integration into a hybrid catalyst or mixing with an OER active catalyst is quite common in literature. [ 4,15–34 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6] Furthermore, its integration into a hybrid catalyst or mixing with an OER active catalyst is quite common in literature. [4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Since the electronic conductivity of metal-oxide catalysts is low compared to metallic catalysts, they are typically mixed with conductive additives and major work on MnO 2 -based catalysts bifunctional air electrodes has been performed in carbon-based systems. [4,12,[15][16][17]22,24,25,[28][29][30][35][36][37][38][39][40][41] However, the long-term stability of carbon-based bifunctional air electrodes is not satisfactory due to the carbon corrosion potential being close to that of the OER.…”
Section: Introductionmentioning
confidence: 99%